Field Performance of Five Soybean Mutants Under Drought Stress Conditions and Molecular Analysis Using SSR Markers - Y Yuliasti; R Reflinur (Atom Indonesia, 2017)
The objectives of this research wereto evaluate (1) the performance of soybean mutant lines under drought stress conditions, and(2) the genetic diversity and relationship among the mutant lines using SSR markers.The field evaluation was conducted during the dry season of 2011 and 2012 at the experimental Farm of Mataram University, West Nusa Tenggara, Indonesia. The field experiment was set up in a randomized block design. Ten mutant lines and two control varieties were evaluated in four replications. Genetic distance among evaluated lines were determined based on allelic diversity analysis using 40 simple sequence repeat (SSR) loci. Under drought stress conditions, two mutant lines, Kdl3 and Kdl8,showed a better performance compared to the other ones. The high yielding mutant lines were Kdl3and Kdl8, which yielded 1.75 t ha-1and 1.69 t ha-1, respectively, compared to the parent and national control, Panderman 1.43 t ha-1 and Muria 1.32 t ha-1. These mutant linesrequired 30.75 to 32days to flower and 79.75 to 83.75 day to harvest with relatively short plant height 28.25 and 23.35 cmrespectively. Those mutant characters were better than those of the other three mutants, the original parents, and the control soybean species. Since the evaluated soybean mutant lines yielded more under drought stress conditions than the standard varieties, they can be used and registered as drought-tolerant soybean mutants. Moreover, the evaluated soybean accessions showed a wide genetic distance. The accessions were clustered into two groups according to their genetic background, namelygroup I (the Panderman with three mutant lines) and group II (the Muria with two mutant lines). Twenty-three out of 40 evaluated SSR loci, including AW31, BE806, CMAC7L, S080, S126, S57, S171, S224, S285, S294, S393, S294, S383, S511, S511, S520, S540, S547, S551, S571, S577, and S578, provided polymorphic alleles between the parents and their mutants and could be used to differentiate mutants from their parents. Therefore, these loci are  informative and may be useful for further analysis of soybean mutant lines in relation to breeding program.